Effects of Quality and Price on Purchase decision Mediated by Brand Image - Rusyda, Hadaina; Syafitri, Lulu Nur’aini; Yoestini (LifeSciFi, 2025)
Local cosmetic brands have evolved to remain competitive in the market as a result of the beauty industry's advancements. The rise of SASC as a regional cosmetics company that can draw in customers. Price and quality are two factors that drive rivalries among brands. Businesses must therefore be able to create strategies that promote favorable customer reactions. The purpose of this study is to ascertain how consumer perceptions of brand image, price, and product quality affect their decisions to buy. The data was gathered using a technique called purposeful sampling. A questionnaire completed by Semarang-based women who had previously purchased SASC yielded 124 samples for this investigation. The AMOS program's SEM analysis was used to process the acquired data. The data analysis results of this study demonstrate that pricing and product quality positively affect the image of the brand and purchasing decisions. Additionally, this study shows that purchase decisions are positively impacted by brand image. Therefore, in order to boost sales, SASC needs to be able to create a brand strategy.